A Novel Model for the Entire Settling–Thickening Process in a Secondary Settling Tank. (1st December 2016) - He, Zhijiang; Zhang, Yuankai; Wang, Hongchen; Qi, Lu; Yin, Xunfei; Zhang, Xiaojun; Wen, Yang
ABSTRACT: : Sludge settling and thickening occur simultaneously in secondary settling tanks (SSTs). The ability to accurately calculate the settling and thickening capacity of activated sludge was of great importance. Despite extensive studies on the development of settling velocity models for use with SSTs, these models have not been applied due to the difficulty in calibrating the related parameters. Additionally, there have been some studies of the thickening behavior of the activated sludge in SSTs. In this study, a novel settling and thickening model for activated sludge was developed, and the model was validated using experimental data (R 2 = 0.830 to 0.963, p < 0.001), which is more reasonable for the characterization of the settling and thickening behavior of the activated sludge in an SST. The application of these models requires only one critical parameter, namely, the stirred sludge volume index SSVI3.5, which is readily available in a water resource recovery facility.